Multi-level supersaturated designs based on error-correcting codes - Georgiou S.; Koukouvinos C.; Mantas P. (Utilitas Mathematica, 2006)
Linear codes can be useful in the construction of multi-level supersaturated designs. Some new construction methods are suggested and supersaturated designs with the equal occurrence property are obtained using these methods. In particular, we can use the qr code-words of the dual C⊥ of a Hamming code Ham(r, q) over GF(q) as the runs of a qr × qr - 1/q - 1 matrix. Applying permutations in each of the columns of this matrix we obtain the desirable design.